Sheffield Doc/Fest Film Festival (2017) - James Mulvey (Alphaville: Journal of Film and Screen Media, 2017)
Sheffield is synonymous with creators and everybody has a story to tell, from the traditional steel workers, to the contemporary brewers of beer, and the futuristic designers of robotics. This was indeed the central theme of the 2017 documentary film festival—documentary as storytelling. This year’s Doc/Fest brought stories from all over the world, through a variety of subthemes, expanding the boundaries of storytelling through the strands of Doc/Adventure, Doc/Expose, Doc/Love, Doc/Rhythm, Doc/Think, Doc/Visions, Doc/Retro, Focus/India, Focus/UK and Alternate Realities. The festival celebrates the art and business of documentaries, promoting both the creativity and the industry of documentary making through screenings, talks, seminars and networking events for filmmakers, delegates and executives. Taking place across fourteen venues, with an average of six screenings per day in each venue, over six days, the festival presented a wide array of offerings addressing social, political, racial, artistic and philosophical subjects. This report will discuss three films and the virtual reality exhibitions as flavours of the storytelling theme of this year’s festival.